Pregnancy and parenting in prison - Shlafer, Rebecca J. (The Oxford handbook of developmental psychology and the law, 2024)
The majority of women involved in the criminal legal system are mothers, and approximately 3% to 4% of women entering prison are pregnant. This chapter explores how developmental science and the law interact and shape the experiences of pregnant women and mothers involved in the criminal legal system and their children before, during, and after incarceration. It considers how several areas of law, including criminal law, family law, and child welfare, coalesce to impact parents and children. The chapter attends closely to relevant principles of developmental science, including sensitive windows of development early in life and the salience of parent–child attachment relationships. The chapter concludes that, with a few exceptions, policies and laws often fail to address the unique needs of parents who are incarcerated and their children. This leaves much room for developmental science to be translated into evidence-based policies and practices to support these families.